Attitudes of Turkish students against markets: Does studying economics matter? - (:unkn) unknown (Emerald Group Publishing Ltd., 2014)
Purpose: The literature shows economics students to be more market oriented than students from other disciplines. A major shortcoming of this work, however, is that it is based on research carried out in the west. The purpose of this paper is to examine the attitudes of Turkish economics students' towards markets.Design/methodology/approach: The study reported here uses a survey developed by Lephard and Breeden to investigate students' attitudes towards markets. The survey consists of 11 market-positive statements and 11 market-negative statements. Participants were asked to indicate their level of agreement with each statement, placed at between 0 and 100 per cent and classified into 11 categories. The survey was administered to economics, physics and mathematics students from different universities. Then, responses of economics students and others are compared.Findings: The results show that Turkish students are less market friendly than their western counterparts. Contrary to the findings of other studies, in Turkey studying economics is found to have no effect on attitudes in this respect.Originality/value: First, almost all of the other studies in this realm are all based on surveys carried out in the west. To the best of the knowledge, this is the first study for other parts of the world. Second, results show that Turkish economics students are less market friendly than their western counterparts, and that studying economics has no significant effect on this. These results are surprising and contrary to the consensus in the literature. © Emerald Group Publishing Limited.
Keywords: Attitudes; Economics education; Values